Association Mapping Analysis of Fatty Acid Content in Different Ecotypic Rapeseed Using mrMLM - Guan, Mingwei; Huang, Xiaohu; Xiao, Zhongchun; Jia, Ledong; Wang, Shuxian; Zhu, Meichen; Qiao, Cailin; Wei, Lijuan; Xu, Xinfu; Liang, Ying; Wang, Rui; Lu, Kun; et al. (Frontiers in Plant Science, 2019)
Brassica napus L. is a widely cultivated oil crop and provides important resources of edible vegetable oil, and its quality is determined by fatty acid composition and content. To explain the genetic basis and identify more minor loci for fatty acid content, the multi-locus random-SNP-effect mixed linear model (mrMLM) was used to identify genomic regions associated with fatty acid content in a genetically diverse population of 435 rapeseed accessions, including 77 winter-type, 55 spring-type, and 303 semi-winter-type accessions grown in different environments. A total of 149 quantitative trait nucleotides (QTNs) were found to be associated with fatty acid content and composition, including 34 QTNs that overlapped with the previously reported loci, and 115 novel QTNs. Of these, 35 novel QTNs, located on chromosome A01, A02, A03, A05, A06, A09, A10 and C02, respectively, were repeatedly detected across different environments. Subsequently, we annotated 95 putative candidate genes by BlastP analysis using sequences from Arabidopsis thaliana homologs of the identified regions. The candidate genes included 34 environmentally-insensitive genes (e.g., CER4, DGK2, KCS17, KCS18, MYB4, and TT16) and 61 environment-sensitive genes (e.g., FAB1, FAD6, FAD7, KCR1, KCS9, KCS12, and TT1), as well as genes invloved in the fatty acid biosynthesis. Among these, BnaA08g08280D and BnaC03g60080D differed in genomic sequence between the high- and low-oleic acid lines, and might thus be the novel alleles regulating oleic acid content. Furthermore, RT-qPCR analysis of these genes showed differential expression levels during seed development. Our results highlight the practical and scientific value of mrMLM or QTN detection and the accuracy of linking specific QTNs to fatty acid content, and suggest a useful strategy to improve the fatty acid content of B. napus seeds by molecular marker-assisted breeding.